(untitled) (Scientific journal of the Fergana State University, 2024)
A systematic approach to the object of study in the researches in linguistics makes it possible to look at the language as a whole macro-system and to divide language units into different substantive groups and to analyze the general and specific aspects of linguistic units in these groups. A number of works have been carried out in world linguistics on the theory of the linguistic field. Nevertheless, there are still unresolved issues regarding the definition of the field, its structure and types. The simultaneous use of the terms semantic field, lexical field, and linguistic field by linguists is the result of such problems. This article analyzes various linguistic features of field theory, including the composition of the semantic field "crime" and the interrelationships of its components. To date, most of the works devoted to the study of the expression of the semantics of "crime" have been carried out within the framework of one language, and there are few works in the hybrid aspect. In this article, the expression of the semantics of "crime" is researched in a comparative-contrastive method based on the field method.